Optimalisasi Pembayangan Fasad dengan Secondary Skin: Pendekatan Arsitektur Tropis pada Desain Balai Besar Wilayah Sungai Bengawan Solo - Taslim , Arif; Widiastuti, Ratih (Nature : National Academic Journal of Architecture, 2024)
Indonesia is a tropical country and has sunshine throughout the year. Therefore, the use of sun shading on the building façade is important. In other hand, Balai Besar Wilayah Sungai Bengawan Solo is one of infrastructures for flood management and control in the Bengawan Solo River area. The current building design uses many wall openings without being equipped with sun shading, allowing the high intensity of sunlight entering the room. Due to this issue, a study was carried out to identify the shading effect on the façade design of Balai Besar Wilayah Sungai Bengawan Solo. Tropical architecture concept was used as a design approach. Simulation method used SketchUp was conducted to compare the effect of before and after secondary skin applied on the façade. The simulation results showed the existing building design had potential to enable high sunlight entering the room. The exposed area to the sunlight was 4 m2 – 11 m2 in the morning and 14 m2 – 31 m2 in the afternoon. While the results after secondary skin was applied on the façade showed a decrease in the area that exposed to the sunlight. It became 2 m2 - 3 m2 or decreased around 33% - 57% in the morning and 3.5 m2 - 8 m2 or decreased around 50% - 60% in the afternoon. Thus, it proves applying secondary skin on the building façade is effectively reducing the intensity of sunlight that enters the room.